Confucius - Tan, Charlene (Continuum library of educational thought, 2013)
Confucius was indisputably a major thinker in education. Charlene Tan's volume offers a coherent account of Confucius' educational thought. This work is divided into three distinctive parts: 1. Intellectual Biography of Confucius 2. Critical Exposition of Confucius' Work 3. Relevance of Confucius' Work Today.